Implementasi Pendidikan Agama Islam pada Kelas Inklusi di SD BPI Kota Bandung - Nissa Nabilla Bakhtiar; Enoh; Nurul Afrianti (Bandung Conference Series: Islamic Education, 2023)
Abstract. The existence of this elementary school that implements inclusive education in the city of Bandung is SD BPI Bandung City. This school is a school where PAI learning is also applied every day for children with special needs. The purpose of this study was to determine the implementation of PAI learning in inclusive classes at BPI Elementary School in Bandung, which includes planning, implementation, assessment and supporting and inhibiting factors for PAI learning. The method used is the Field Research method using an inductive approach. The results obtained from this study are: In planning lessons, PAI teachers make lesson plans for regular students while special accompanying teachers make Individual Learning Programs for students with special needs. In the implementation of learning, the PAI teacher teaches as usual, there is no special action to pay attention to the needs of students with special needs, because there is a special accompanying teacher in the class who functions to guide and create learning methods for students with special needs, if the method used by the PAI teacher cannot be followed by ABK students. The questions and assessment formats prepared by the PAI teacher are only for regular students, while for students with special needs it is made by a special accompanying teacher. Supporting factors that support inclusive learning in this school are the competence of the principal, teachers and an environment that is ready to accept students with special needs. The inhibiting factors in the implementation of Islamic religious education learning include: the lack of planning carried out by the teacher, students with special needs often have difficulty understanding the material and answering practice questions. Abstrak. Keberadaan sekolah dasar ini salah satu yang menerapkan pendidikan inklusif di kota Bandung adalah SD BPI Kota Bandung. Sekolah ini merupakan sekolah yang dimana dalam pembelajaran PAI juga diterapkan sehari hari bagi anak ABK. Tujuan penelitian ini adalah untuk mengetahui implementasi pembelajaran PAI pada kelas inklusif di SD BPI Kota Bandung, yang mencakup perencanaan, pelaksanaan, penilaian dan faktor pendukung dan penghambat pembelajaran PAI. Metode yang digunakan adalah metode Field Research dengan menggunakan pendekatan induktif. Hasil yang diperoleh dari penelitian ini adalah: Dalam merencanakan pembelajaran, guru PAI membuat RPP untuk siswa reguler sedangkan guru pendamping khusus membuat Program Pembelajaran Individual untuk siswa ABK. Dalam pelaksanaan pembelajaran, guru PAI mengajar seperti biasa, tidak ada tindakan istimewa untuk memperhatikan kebutuhan siswa ABK, karena terdapat guru pendamping khusus di dalam kelas yang berfungsi untuk membimbing dan membuat metode pembelajaran bagi siswa ABK, apabila metode yang digunakan guru PAI tidak dapat diikuti oleh siswa ABK. Pembuatan soal dan format penialaian yang disiapkan oleh guru PAI hanya untuk siswa reguler sedangkan bagi siswa ABK dibuat oleh guru pendamping khusus. Faktor pendukung yang menunjang pembelajaran inklusif di sekolah ini yaitu kompetensi kepala sekolah, guru-guru dan lingkungan yang siap untuk menerima siswa ABK. Adapun faktor penghambat dalam implementasi pembelajaran pendidikan agama Islam diantaranya: kurangnya perencanaan yang dilakukan oleh guru, siswa berkebutuhan khusus seringkali kesulitan dalam memahami materi dan menjawab soal latihan.